2003
DOI: 10.1097/00000542-200309000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Neuromusclar Blockade and Simultaneous Increase in Plasma Rocuronium Concentration after the Intravenous Infusion of the Novel Reversal Agent Org 25970

Abstract: The authors propose that the capture of rocuronium by Org 25969 causes the rapid reversal of neuromuscular block. The reversal can be explained by the rapid transfer of free rocuronium from the effect compartment (neuromuscular junction) to the central compartment, in which it is bound to Org 25969. This explains the increase in total plasma concentration of rocuronium (free and bound to Org 25969).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
81
0
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(91 citation statements)
references
References 6 publications
2
81
0
7
Order By: Relevance
“…To the Editor, Sugammadex specifically antagonizes the steroidal neuromuscular blocking agent (NMBA), rocuronium, 1 and it also has affinity for other steroidal NMBAs. A period of 24 hr is currently recommended before re-administering rocuronium after sugammadex.…”
mentioning
confidence: 99%
“…To the Editor, Sugammadex specifically antagonizes the steroidal neuromuscular blocking agent (NMBA), rocuronium, 1 and it also has affinity for other steroidal NMBAs. A period of 24 hr is currently recommended before re-administering rocuronium after sugammadex.…”
mentioning
confidence: 99%
“…These fresh rocuronium molecules in plasma are soon bound to sugammadex, and the interstitial tissue, where the neuromuscular junction lies, is rapidly depleted of its rocuronium molecules. Evidence for this process can be found in a study by Epemolu et al,8 who demonstrated that, consistent with the above hypothesis, sugammadex was associated with an increase of total (free plus bound) plasma concentration of rocuronium.…”
mentioning
confidence: 56%
“…[8][9][10][11] One may criticize the studies because of the choice of accelerometry, which overestimates the degree of recovery, but this drawback is minor considering how effective sugammadex is compared with either placebo or neostigmine. In most clinical circumstances, the time interval from blockade until full recovery is not expected to be particularly critical.…”
mentioning
confidence: 99%
“…Binding is rapid, and steroidal NMBs show a high affinity for sugammadex, especially rocuronium and to a lesser degree vecuronium. 8 Beyond the rapid reversal of NMBs allowed by sugammadex, 7 neutralizing the NMB molecules by masking the causal allergen (i.e., the quaternary ammonium ion) should also be considered when an NMB-related allergic event is suspected. This hypothesis was reported for the first time through a case report.…”
mentioning
confidence: 99%
“…La fixation est rapide et l'affinité des curares stéroïdiens pour le sugammadex est élevée, surtout pour le rocuronium, et à un moindre degré pour le vécuronium. 8 Au-delà de la levée du bloc neuromusculaire rapide que permet le sugammadex, 7 il pourrait être envisageable de neutraliser les molécules d'un curare stéroïdien en cas de suspicion d'accident allergique lié à celui-ci en masquant l'allergène responsable, en l'occurrence l'ion ammonium quaternaire. Cette hypothèse a été rapportée pour la première fois grâce à la publication d'un cas clinique.…”
unclassified